Effect of suspension training on the balance ability of surfers without relying on vision - Wang, Zhaoyi; Zhou, Jiayang; Ma, Yong; Guo, Zhihao; Jia, Mengyao; Zheng, Weitao (Frontiers in Physiology, 2025)
BackgroundSurfing is an emerging Olympic sport that requires athletes to have excellent balance without relying on vision. This study introduces TRX (Total Resistance Exercise) suspension training into the balance training of surfing programs to investigate its effectiveness on the surfers’ balance ability without relying on vision.MethodsThirty-two surfers from the Chinese National Surfing Team were randomly divided into a TRX group and a traditional balance training (TB) group, and the two groups were given intervention training for about 30 min three times a week for 8 weeks. Eye-closed one-leg stand and linear travel deviation tests were performed at different experiment stages to examine static and dynamic balance changes without visualization.ResultsAfter intervention, both groups significantly improved left/right foot static balance (eyes-closed single-leg standing time) (F = 21.26 and 25.22, p < 0.001), with no significant inter-group or group × time interaction effects (all p > 0.05). For dynamic balance (linear travel deviation), both groups improved significantly with intervention (F = 23.41, p < 0.001), and inter-group difference was significant (F = 4.65, p = 0.039); the TRX group had smaller deviation than the TB group at E2 (5 weeks post-intervention, p = 0.021) and E3 (8 weeks post-intervention, p < 0.001), with a significant group × time interaction (F = 3.36, p < 0.05), showing better improvement in the middle-late intervention stage.ConclusionTRX and TB were effectively able to improve surfers’ non-vision-dependent balance ability. However, TRX was more effective in improving dynamic balance in that situation. TB and TRX can be used to improve the static balance ability and dynamic balance ability for the first 5 weeks, and TRX can be applied to the balance training of surfers after 5 weeks.